Accessibility for wheelchair users in public parks : a comparison between Adelaide and Kuantan - Liyana, Mohamed Yusof (2010)
This study investigated the accessibility of wheelchairs users in public parks in Kuantan, Malaysia and Adelaide, South Australia. Anthropology of wheelchairs users locally is identified comprehensively. The investigation takes into consideration the needs and difficulties of wheelchairs users to access public parks as well as fundamental facilities required by wheelchair user in public parks. An inclusive study on Malaysian legislation, The Persons with Disabilities Act 2008, Australian legislation, Disability Discrimination Act 1992, Malaysian Standard MS 1184:2002, Australia Standard AS 1428.1-2001 and policies and guidelines used by Majlis Perbandaran Kuantan (MPK) and Adelaide City Council (ACC) when planning for people with disabilities specifically wheelchair users is undertaken. The effectiveness of these governments documents is analysed and compared by conducting observation and documentation on accessibility in selected public parks in Kuantan and Adelaide. Esplanade Park, Kerang Park, Karrawirra-Park 12 Parade Grounds Park and Elder Park are chose to serve as case studies. Comparison on the observations and documentations conducted between these four parks found that the Australian government document is more effective when compared to Malaysian government documents. The study also found, in providing accessibility for wheelchair users in public parks, common issues such as budgets, conflicts with infrastructure, conflicts with other disabilities, natural factors, effectiveness of government documents, and lack of awareness arise in both states. However the issues in Kuantan are more critical.